The anti-inflammatory mechanism of thymosin β4 in a RAW 264.7 macrophage inflammation model - WU Tianyu, LIN Yujun, LIN Xiaoyu, ZHU Yi, YU Muxue, LIU Wangkai (Xin yixue)
Objective To explore the effects of Thymosin β4 （Tβ4） on the lipopolysaccharide （LPS）-induced polarization tendency of murine monocyte-macrophage RAW264.7 cells and its influence on inflammatory responses. Methods An inflammation model was established by LPS induction in RAW264.7 cells. Cell viability was assessed using the CCK-8 assay. The concentrations of cytokines [tumor necrosis factor-α （TNF-α） and interleukin-6 （IL-6）] were detected by enzyme-linked immunosorbent assay （ELISA）. Nitric oxide （NO） secretion in the cell culture supernatant was detected using the Griess method. Real-time quantitative polymerase chain reaction （RT-qPCR） was employed to detect mRNA expression levels of nuclear factor-κB （NF-κB）， cyclooxygenase-2 （COX-2）， TNF-α， and IL-6. Western blotting was used to analyze protein levels of inducible nitric oxide synthase （iNOS）， NF-κB， phosphorylated NF-κB （p-NF-κB）， NF-κB inhibitor α （IκB-α）， and phosphorylated IκBα （p-IκB-α）. The polarization status of macrophages was observed using double fluorescence staining. Immunofluorescence staining was performed to examine NF-κB localization and expression. Results After treatment with 1 000 μg/L Tβ4 for 24 hours， the cell viability of RAW 264.7 cells was 90.2%， showing a statistically significant difference compared to the blank control group （P < 0.05）. Tβ4 at various concentrations effectively inhibited NO production （all P < 0.000 1）. Tβ4 decreased the concentrations of pro-inflammatory cytokines（TNF-α and IL-6） and NO in the LPS-induced RAW264.7 inflammatory model. It also downregulated mRNA expression of NF-κB， COX-2， TNF-α， and IL-6， as well as protein expression of iNOS， p-NF-κB， and p-IκBα. Additionally， Tβ4 inhibited NF-κB nuclear translocation and decreased CD80 expression （all P < 0.05）. Conclusion Tβ4 exhibits anti-inflammatory effects， the mechanisms of which may be associated with the inhibition of the NF-κB signaling pathway and suppression of macrophage M1 polarization.